From the 'woman's point of view' ten years later: Towards a feminist organization studies - Calas, Marta B.; Smircich, Linda (The Sage Handbook of Organization Studies, 2006)
Keywords: OFDIG; approches et analyses; discipline; femmes*; féminisme matérialiste; féminisme radical; genre; identités LGBTQIA2+; organisation; post-structuralisme; psychanalyse; ressource en ligne; sciences de la gestion; thématiques; économie

Measuring care: Gender, empowerment, and the care economy - Folbre, Nancy (Journal of Human Development, 2006)
How should “care” be defined and measured in ways that enhance our understanding of the impact of economic development on women? This paper addresses this question, suggesting several possible approaches to the development of indices that would measure gender differences in responsibility for the financial and temporal care of dependents.
Keywords: care; discipline; macroéconomie; projet charge mentale; périodes; sciences de la gestion; soins aux personnes dépendantes; thématiques; travail; travail invisible; économie